Factors affecting gold price in Malaysia / Erliana Sazni Mohammad - Mohammad, Erliana Sazni (Faculty of Business and Management, 2017)
The aim of this study is to examine factors affecting of gold price in Malaysia. This paper examines whether the changes trend of the gold price in Malaysia will give an impact on crude oil price, inflation rate, exchange rate, and interest rate. Over the past few years, the gold price in Malaysia has experienced the significant price expansion. The study will explain more about the relationship between the gold price and the independent variables for 30 years. In the process of findings there are few types of analysis were tested using E-views Version 7.0, such as multiple linear regression, single linear regression descriptive statistics, unit root tests, and more. The result indicates that there are significantly related to gold price. This study can be useful for students, university, investors and buyers, and the Government to know which factors that affect gold price in Malaysia.